2015
DOI: 10.1111/aor.12415
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Simulation of Mass Transfer in Artificial Kidneys

Abstract: In this work, the three-dimensional velocity and concentration fields on both the blood and dialysate sides in an artificial kidney were simulated, taking into account the effects of the flow profiles induced by the inlet and outlet geometrical structures and the interaction between the flows of blood and dialysate. First, magnetic resonance imaging experiments were performed to validate the mathematical model. Second, the effects of the flow profiles induced by the blood and dialysate inlet and outlet geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…In line with these considerations, sodium diffusion across the membrane was modeled as porous media transport, according to theoretical equations [9 and 10]. The Millington and Quirk model (28) was chosen for calculation of the effective diffusivity, as reported in (11). Islam et al (8) estimated porosity for each of the 3 layers composing the membrane of a Polyflux 210H hemodialyzer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these considerations, sodium diffusion across the membrane was modeled as porous media transport, according to theoretical equations [9 and 10]. The Millington and Quirk model (28) was chosen for calculation of the effective diffusivity, as reported in (11). Islam et al (8) estimated porosity for each of the 3 layers composing the membrane of a Polyflux 210H hemodialyzer.…”
Section: Methodsmentioning
confidence: 99%
“…In 2-dimensional (2D) models, flow and/or concentration fields are computed on a bi-dimensional surface representing the axial and radial directions of the blood-membrane-dialysate interface (48). Three-dimensional (3D) models are also reported in the literature (911). Models with higher levels of abstraction describe the kinetics of body pools for substances like urea or sodium with ordinary differential equations (ODEs) (3, 1216).…”
Section: Introductionmentioning
confidence: 99%
“…Weiping Ding et al of the University of Science and Technology of China, Hefei, Anhui, China simulated the three‐dimensional velocity and concentration fields on both the blood and dialysate sides in an artificial kidney. Their results showed that as the blood flow rate increases, the flow field on the blood side becomes less uniform; however, as the dialysate flow rate increases, the flow field on the dialysate side becomes more uniform.…”
Section: Renal Supportmentioning
confidence: 99%
“…In the last years, three-dimensional (3-D) models have been developed, based on the concept that the fiber bundle can be treated as two interpenetrating porous media. For example, Ding et al [22] used their model to investigate the effects on mass transfer of inlet and outlet geometrical structures and of the distribution tabs [23]. Also Cancilla et al [24] developed a model that falls into this category for studying the influence of the most relevant parameters and of the operating conditions on the dialyzer's efficiency.…”
Section: Introductionmentioning
confidence: 99%